Effects of Mind Mapping, Cooperative Learning, and Learning Motivation on Elementary Students' Explanatory Text Retelling Achievement - Lely Ardianingsih; Achmad Noor Fatirul; Cindy Asli Pravesti (Murhum : Jurnal Pendidikan Anak Usia Dini, 2026)
Low learning outcomes in retelling explanatory texts remain a major challenge in Indonesian language learning among elementary school students, particularly in comprehending text content, organizing information, and presenting ideas coherently. This study examined the effects of Mind Mapping and Cooperative Learning methods, as well as learning motivation, on the learning outcomes of fifth-grade students. A quantitative experimental approach was employed using a Non-equivalent Control Group Design with a 2 × 2 factorial model. The sample consisted of 52 students divided into an experimental group taught through Mind Mapping and a comparison group taught through Cooperative Learning. Data were collected through learning outcome tests and learning motivation questionnaires and analyzed using Two-Way ANOVA. The findings revealed that Mind Mapping produced significantly better learning outcomes than Cooperative Learning. Learning motivation also significantly influenced learning outcomes, and a significant interaction was found between learning methods and motivation. These results highlight the importance of visual-based instructional strategies and motivational support in improving elementary Indonesian language learning.